2017
DOI: 10.1108/jfc-03-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Linking earnings management practices and corporate governance system with the firms’ financial performance

Abstract: Purpose In the shadow of global financial crisis, practice of earnings management can be hazardous for the growth and development of an economy, especially for a developing economy like India. This empirical study is performed to analyse the presence of earnings management practices in Indian public and private commercial banking industry. This study also aims at developing a framework for the three-way relationship existing between the variables of corporate governance, earnings management practices and firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 59 publications
4
40
1
6
Order By: Relevance
“…The presence of INDs is important for performing a better monitoring role, which helps to achieve a higher profitability, as suggested by agency theory . Board independence as a vital corporate governance attribute promotes profitable growth through positively influencing the performance of banks (Kumari and Pattanayak 2017). Financial performance can be attained with a more independent board (Dalton et al 1998), as it performs a better monitoring role (Carter et al 2010) because independent directors are alleged to be effective monitors (Adams et al 2010).…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of INDs is important for performing a better monitoring role, which helps to achieve a higher profitability, as suggested by agency theory . Board independence as a vital corporate governance attribute promotes profitable growth through positively influencing the performance of banks (Kumari and Pattanayak 2017). Financial performance can be attained with a more independent board (Dalton et al 1998), as it performs a better monitoring role (Carter et al 2010) because independent directors are alleged to be effective monitors (Adams et al 2010).…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…This suggests that, in order to establish an effective corporate governance framework, director compensation is essential (Chang et al 2015), because investment in human capital is one of the main drivers which helps to achieve the sustainable growth of banks (Nawaz 2017). Therefore, director compensation helps to improve the performance of banks (Kumari and Pattanayak 2017). Moreover, director compensation also helps to minimize agency problems, because directors act as the agents of shareholders (principals) in order to protect and maximize their wealth.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…A good CG can build credibility, transparency, and accountability that enhances firm performance. A strong CG structure will also control managerial decision-making and improve financial reporting quality, thereby increasing firm value (Kumari & Pattanayak, 2017). In its implementation, CG must recognize the rights of shareholders, including employees, suppliers and customers (Kolsi & Grassa, 2017).…”
Section: Rq 1: Do Icd and Cg Have A Role In Accounting-based Performamentioning
confidence: 99%
“…Agency theory also suggests that a firm needs to invent a CG mechanism that pushes behavior to align with the result as desired by the owner (Bendickson et al, 2016). Kumari and Pattanayak (2017) found that weak CG and EM practices are the initial signs that point to the weakening of the firm's financial health and increased risk of bankruptcy. Daghsni et al (2016) found a negative association between CG and NDNI, while Buniamin et al (2012) discovered a positive relationship between CG and EM through DA, where a large number of women on board can increase DA.…”
Section: The Effect Of Corporate Governance (Cg) On Accounting-based mentioning
confidence: 99%
See 1 more Smart Citation